2010
DOI: 10.1093/jnci/djq524
|View full text |Cite
|
Sign up to set email alerts
|

Gene Pathways Associated With Prognosis and Chemotherapy Sensitivity in Molecular Subtypes of Breast Cancer

Abstract: Different biological processes were associated with prognosis and chemotherapy response in ER-positive and ER-negative breast cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
171
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(182 citation statements)
references
References 31 publications
10
171
0
1
Order By: Relevance
“…In our hands, when used at a final concentration of 5 µM, neither drug was able to block persistent EGFR tyrosine phosphorylation in lapatinib resistant cells-maintained in 1 µM lapatinib-nor did they restore lapatinib sensitivity ( Figure 6A and B). Neratinib, in contrast to lapatinib, gefitinib and erlotinib is an irreversible EGFR and HER2 TKI [43]. Consistent with previous reports [43], we found that neratinib was a potent inhibitor of parental HER2+ breast cancer cells (Additional file 7).…”
Section: Egfr Represents An Attractive Target In Lapatinib Resistant supporting
confidence: 89%
See 1 more Smart Citation
“…In our hands, when used at a final concentration of 5 µM, neither drug was able to block persistent EGFR tyrosine phosphorylation in lapatinib resistant cells-maintained in 1 µM lapatinib-nor did they restore lapatinib sensitivity ( Figure 6A and B). Neratinib, in contrast to lapatinib, gefitinib and erlotinib is an irreversible EGFR and HER2 TKI [43]. Consistent with previous reports [43], we found that neratinib was a potent inhibitor of parental HER2+ breast cancer cells (Additional file 7).…”
Section: Egfr Represents An Attractive Target In Lapatinib Resistant supporting
confidence: 89%
“…Neratinib, in contrast to lapatinib, gefitinib and erlotinib is an irreversible EGFR and HER2 TKI [43]. Consistent with previous reports [43], we found that neratinib was a potent inhibitor of parental HER2+ breast cancer cells (Additional file 7). Neratinib, when used at higher concentrations than in parental cell cultures, inhibited persistent phosphorylation of EGFR, HER3 and Akt T308 in resistant cells, triggering cell apoptosis (increased cleaved PARP), and inhibition of cell growth and viability (P < 0.0008 in rSKBR3; P < 0.0025 in rBT474) ( Figure 6A and B).…”
Section: Egfr Represents An Attractive Target In Lapatinib Resistant supporting
confidence: 89%
“…pCR was defined as loss of the invasive component of the primary tumor in one study (33) and no residual invasive cancer in the breast and axillary lymph nodes in other seven studies (34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…We further evaluated whether AR mRNA expression were associated with response to neoadjuvant CT (anthracyclines AE taxanes). Out of 1,005 patients from eight datasets (33)(34)(35)(36)(37)(38), 235 (23%) patients achieved pCR, 765 (76%) did not, while five samples were inadequate for the analysis. High AR expression levels showed significant association with lower pCR rate (OR, 0.57; 95% CI, 0.44-0.74, P < 0.001) in the univariate analysis while not significant in a multivariate model (OR, 0.74; 95% CI, 0.54-1.01, P ¼ 0.063; Fig.…”
Section: Prognostic Significance Of Ar Expressionmentioning
confidence: 99%
“…The more proliferative tumours are associated with a beneficial response towards the chemotherapy [54].…”
Section: Chemotherapymentioning
confidence: 99%